2016
DOI: 10.1039/c6tx00166a
|View full text |Cite
|
Sign up to set email alerts
|

Gender specific differences in the liver proteome of rats exposed to short term and low-concentration hexabromocyclododecane (HBCD)

Abstract: Gender specific impact of HBCD on rat liver proteome, determined by 2D-DIGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The animal experiment was detailed in [1] , [2] and approved under number 2006-051 by the Animal Welfare Committee of Wageningen University. In brief, male Wistar WU (HsdCpbWU) rats with normal or reduced thyroid function (hypothyroid) were orally exposed to 0, 3 or 30 mg/kg bw/d HBCD, respectively, for 7 consecutive days.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The animal experiment was detailed in [1] , [2] and approved under number 2006-051 by the Animal Welfare Committee of Wageningen University. In brief, male Wistar WU (HsdCpbWU) rats with normal or reduced thyroid function (hypothyroid) were orally exposed to 0, 3 or 30 mg/kg bw/d HBCD, respectively, for 7 consecutive days.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Rat liver lysates were subjected to two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) as previously described, without modifications, to make it compatible to the previously performed study in females [1] , [2] , [3] . This comprised a classical 2D-DIGE experiment, by separating CyDye-labeled proteins from liver lysates in a non-linear 3–10 pH-range and subsequently in large-format SDS-PAGE gels (260×200×1 mm).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater susceptibility of females than males to develop diabetes has been ascribed to lower insulin secretion, more severe liver damage and larger impairment of regulation of sex hormones as well as lower glucose tolerance and higher blood glucose levels (Chaudhari and Yun 2014). Studies on HBCD and other BFRs were in part based on the fact that for these compounds sex-dependent effects on body and organ weights and on thyroid hormone levels were reported, suggesting that female rats may be more sensitive than males (Miller et al 2016). The study reported by Schwab et al (Schwab et al 2011) on effects of dietary genistein on sex differences in protein abundance in mice was based on the elevated cardiovascular risk in especially postmenopausal women.…”
Section: Sex Dependent Effectmentioning
confidence: 99%